2021
DOI: 10.1186/s13048-020-00760-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-362-3p acts as a tumor suppressor by targeting SERBP1 in ovarian cancer

Abstract: Background Ovarian cancer is the leading lethal gynecological cancer and is generally diagnosed during late-stage presentation. In addition, patients with ovarian cancer still face a low 5-year survival rate. Thus, innovative molecular targeting agents are required to overcome this disease. The present study aimed to explore the function of miR-362-3p and the underlying molecular mechanisms influencing ovarian cancer progression. Methods The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Regarding ovarian cancer, only one study revealed that miR-362-3p levels were downregulated in the tissues and cells, which could suppress cell growth and migration by reducing MyD88 expression [10] . Additionally, recent studies have also shown that miR-362-3p inhibits ovarian cancer and inhibits the occurrence and development of ovarian cancer by directly binding its target gene, SERPINE1 mRNA-binding protein 1 ( SERBP1 ) [26] . Similar to a previous study, miR-362-3p levels were also significantly downregulated in ovarian cancer tissues and cells in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ovarian cancer, only one study revealed that miR-362-3p levels were downregulated in the tissues and cells, which could suppress cell growth and migration by reducing MyD88 expression [10] . Additionally, recent studies have also shown that miR-362-3p inhibits ovarian cancer and inhibits the occurrence and development of ovarian cancer by directly binding its target gene, SERPINE1 mRNA-binding protein 1 ( SERBP1 ) [26] . Similar to a previous study, miR-362-3p levels were also significantly downregulated in ovarian cancer tissues and cells in our study.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Cao et al have found the suppressive role of miR-362-3p in the function of ovarian cancer cells. 11 In breast cancer, miR-362-3p inhibits the cell proliferation. 28 Thus, we consider that miR-362-3p serves as a suppressor in NPC progression.…”
Section: Discussionmentioning
confidence: 99%
“… 8 There have been numerous studies reporting the important roles of miRNAs in human malignancies. 9 , 10 In addition, microRNA (miR)-362-3p has been found to function as a tumor suppressor in multiple tumor diseases, such as ovarian cancer, 11 epithelial ovarian cancer 12 and cervical cancer. 13 However, its role in NPC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin delivery based on nanocarriers is conductive to reducing drug-protein interaction to achieve selective accumulation on tumor sites. 52 In addition, the proportion in G0/G1 phase in the αCD97-USPIO-Au-DDP group increased more remarkably, because αCD97 modification enhanced the targeting of the compound drug to cancer cells. All the above, αCD97-USPIO-Au-DDP was capable of blocking cancer cells in G0/G1 phase to restrain cell proliferation.…”
Section: Characterization Of Morphology and Physical And Chemical Propertiesmentioning
confidence: 97%